Cumulative life course impairment in patients with dermatological diseases, with a focus on psoriasis - Ricardo Romiti; Renata Ferreira Magalhães; Gleison Vieira Duarte (Sociedade Brasileira de Dermatologia, 2024)
Abstract The concept of "Cumulative Life Course Impairment" (CLCI) characterizes the set of factors harmful to the lives of patients resulting from the stigma and physical and psychological impairment associated with different chronic diseases, which can accumulate irreversibly over the course of patients lives. The sum of these factors often makes it impossible for these individuals to enjoy their lives fully, intensely and adequately. On the other hand, CLCI also incorporates coping strategies, including external factors and personality characteristics, which may act as modulating or protective factors of vulnerability to the CLCI. Although psoriasis is the most studied dermatological disease in relation to its impact on quality of life and CLCI, several other chronic inflammatory diseases such as atopic dermatitis, hidradenitis suppurativa, and alopecia areata have also been evaluated in relation to the magnitude of the damage to patients lives.